Tumor regression of multiple bone metastases from breast cancer after administration of strontium-89 chloride (Metastron). Issue 4 (10th May 2014) - Heianna, Joichi; Miyauchi, Takaharu; Endo, Wataru; Miura, Naoki; Terui, Kazuyuki; Kamata, Syuichi; Hashimoto, Manabu
We report a case of tumor regression of multiple bone metastases from breast carcinoma after administration of strontium-89 chloride. This case suggests that strontium-89 chloride can not only relieve bone metastases pain not responsive to analgesics, but may also have a tumoricidal effect on bone metastases.